Living in a high temperature geothermal area : the impact of geothermal energy on the architecture, townscape and society of Hveragerði - Ásta Sóllilja Þorsteinsdóttir 1991- (2017)
Hveragerði is a small town in the southwest part of Iceland. Hveragerði is situated at the edge of a high temperature geothermal area known as Hengill-region. Living in a high temperature geothermal area has its advantages, the most important being the geothermal energy. It can also be challenging to live in such unstable environment where earthquakes are ordinary and hot springs come and go. The name of the town Hveragerði, translates in English to “a place of hot springs” and was first given to the geothermal park, an area of hot springs, that the town is built around. Geothermal energy has always been a key factor in the economy of Hveragerði and the town has long been known for greenhouse farming and health. Nowadays the greenhouses are retreating and there is an increasing need for residential housing and service for tourists. The purpose of this research is to explore the impact of geothermal energy on the architecture and townscape of Hveragerði, as well as to explore the social aspects of living in a high temperature geothermal area.